Difusi Inovasi Pemberdayaan Nelayan Rajungan Berkelanjutan di Kabupaten Lampung Timur - Wulandari, Fitria; Gultom, Dame Trully; Gitosaputro, Sumaryo; Seopraktikno, Serly Silviyanti (Suluh Pembangunan : Journal of Extension and Development, 2025)
One of the leading commodities that supports the national fisheries sector is crab (Portunus pelagicus). Lampung Province was selected as the first province to become a pilot project for sustainable crab fisheries management by the Ministry of Marine Affairs and Fisheries (KKP). East Lampung Regency has a vital role in the sustainability of the national crab industry. Crab fishermen in East Lampung still face various structural and technical challenges. The community empowerment approach for fishermen has become one of the main strategies in sustainable crab fisheries management. The success of the empowerment program is highly dependent on the extent to which the innovations introduced can be accepted and adopted by the target community. This study aims to determine the level of diffusion of sustainable crab fishermen empowerment innovations.. The research location was chosen intentionally (Purposive), namely Margasari Village and Muara Gading Mas Village, Labuhan Maringgai District, East Lampung Regency. This research was conducted in May-June 2025. The population was 292 crab fishermen and the research sample was 75 crab fishermen. The data used were primary data and secondary data. The data analysis method used was descriptive. The results of the study were the level of diffusion of innovation in empowering crab fishermen in the catch quota approach included in the low category, diffusion of innovation in the supervision and law enforcement approach included in the medium category, diffusion of innovation in the restocking and conservation approach included in the low category, diffusion of innovation in the fair and sustainable market approach included in the medium category, and diffusion of innovation in the GPS technology approach included in the high category.